The Role of Social Media Marketing, Brand Awareness, and Customer Engagement in Enhancing MSME Competitiveness - Gesty Ernestivita; Euphrasia Suzy Suhendra; Subagyo (Journal Management & Economics Review (JUMPER), 2026)
This study aims to examine the role of social media marketing, brand awareness, and customer engagement in enhancing the competitiveness of Micro, Small, and Medium Enterprises (MSMEs). A quantitative research approach was employed, utilizing a cross-sectional survey design, with data collected from 200 MSME owners who actively use social media platforms for business activities. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the proposed hypotheses. The results reveal that social media marketing has a significant positive effect on MSME competitiveness, both directly and indirectly. Furthermore, social media marketing significantly influences brand awareness and customer engagement, which in turn positively affects competitiveness. The findings also confirm that brand awareness and customer engagement act as significant mediating variables in the relationship between social media marketing and MSME competitiveness. These results highlight the importance of adopting integrated digital marketing strategies that focus not only on promotional activities but also on building strong brand identity and fostering customer relationships. This study contributes to the existing literature by providing a comprehensive framework that explains how digital marketing practices can enhance MSME competitiveness. Practically, the findings offer valuable insights for MSME owners and policymakers in developing effective strategies to improve business performance in the digital era.